Social behavioral impairments in SYNGAP1-related intellectual disability - Naveed, Hajer; McCormack, Maria; Holder, J. Lloyd (Frontiers in Pediatrics, 2023)
Synaptopathies are neurodevelopmental disorders caused by genetic mutations disrupting the development and function of neuronal synapses. We administered the validated Social Responsiveness Scale, Second Edition (SRS-2) to investigate the phenotypic presentation of social-behavioral impairments for the developmental synaptopathy-SYNGAP1-related Intellectual Disability (SYNGAP1-ID) (n=32) compared with a phenotypically similar disorder Phelan-McDermid Syndrome (PMD) (n=27) and healthy controls (n=43). A short form SRS-2 analysis (n=85) was also conducted. Both SYNGAP1-ID and PMD had significantly elevated total and subcategory T-scores, with no significant score differences between SYNGAP1-ID and PMD, consistent between the full and short form. Mild to severe deficiencies in reciprocal social behavior were found in 100% of PMD individuals and 87.1% of SYNGAP1-ID individuals.Additionally, the short form demonstrated greater utility for SYNGAP1-ID participants due to lower item-omission rates. Surprisingly, a positive correlation between age and total score was discovered for SYNGAP1-ID participants and not found in individuals with PMD or healthy controls. In conclusion, significant impairment in reciprocal social behaviors is highly prevalent in SYNGAP1-ID.